Pengembangan Perangkat Pembelajaran Model Inkuiri Terbimbing Berbantu Media PhET untuk Meningkatkan Kemampuan Pemecahan Masalah dan Keterampilan Generik Sains Fisika Peserta Didik - Nurjannah, Eka; Ayub, Syahrial; Doyan, Aris; Sahidu, Haerunisyah (Mataram University, 2021)
The purpose of this study is to determine the feasibility, practicality, and effectiveness of phET media-assisted incuquencing model learning tools to improve problem solving skills and generic skills of student physics design. The research design used is Research and Development (R&D) design with 4D Model (define, design, develop, &disseminate). The learning tools developed include: syllabus, Lesson Plan, Student worksheet, Test instruments, and PhET media. The feasibility data of the defense device is obtained from the validation results of 3 expert validators and 3 practitioner validators. Validation results show syllabus, Lesson Plan, test instruments and Media PhET in very valid category and Student worksheet valid category. The reliability of the learning pre-level with an average of 92.3 % indicates that all components assessed are in the realiabel category. The practicality of learning skills is projected from the results of teacher responses, the implementation of learning is in the category of very practical and the response of learners with practical categories. The effectiveness of learning skills based on N-gain problem solving skills and generic skills of physics science learners, obtained an average of N-gain of 77 and 78 respectively with a highly effective category. Based on these results, it was concluded that the learning skills of the phet media-assisted incugate model are feasible, practical and effective to improve problem solving skills and generic skills of the students' physics